Anne Frank - McDonough, Yona Zeldis; Zeldis, Malcah (New York : Henry Holt and Company, 1997)
Traces the life of a Jewish girl who chronicled her day-to-day life in a diary as she hid in an attic in Nazi-occupied Holland for two years.
Keywords: Frank, Anne, -- 1929-1945 -- Juvenile literature; Frank, Anne, -- 1929-1945.; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam; Jewish children in the Holocaust -- Biography -- Juvenile literature -- Netherlands -- Amsterdam; Jews -- Biography -- Netherlands; Women -- Biography; Amsterdam (Netherlands) -- Biography -- Juvenile literature